Culture : the story of us, from cave art to K-pop - Puchner, Martin, 1969- (W.W. Norton & Company, 2023)
"What good are the arts? Why should we care about the past? For millennia, humanity has sought to understand and transmit to future generations not just the "know-how" of life, but the "know-why"--The meaning and purpose of our existence, as expressed in art, architecture, religion, and philosophy. This crucial passing down of knowledge has required the radical integration of insights from the past and from other cultures. In Culture, acclaimed author, professor, and public intellectual Martin Puchner takes us on a breakneck tour through pivotal moments in world history, providing a global introduction to the arts and humanities in one engaging volume"--